2020
DOI: 10.1136/esmoopen-2019-000621
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine combined with 5-hydroxytryptamine type 3 receptor antagonist (5-HT3 RA) plus dexamethasone for prevention and treatment of chemotherapy-induced nausea and vomiting in high and moderate emetogenic chemotherapy: a systematic review and meta-analysis of randomised controlled trials

Abstract: We performed a pooled analysis to evaluate the efficacy and adverse events (AEs) of olanzapine combined with dexamethasone plus 5-hydroxytryptamine type 3 receptor antagonist (5-HT3 RA) compared with 5-HT3 RA plus dexamethasone for the prevention and treatment of chemotherapy-induced nausea and vomiting (CINV) in high and moderate emetogenic chemotherapy based on randomised controlled trials (RCTs). PubMed, EMBASE, Web of Science, the Cochrane Library, China Biomedical Literature database (CBM), WanFang Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…This review also has the highest statistical power and appraises all the clinically important endpoints. The most recent reviews by Zhou et al in 2020 included 11 studies with 1107 patients [ 21 ]; other reviews by Bahbah et al in 2019 and Sutherland et al in 2018 included 9 RCTs with 1572 patients, and 14 trials with 1917 participants, respectively [ 22 , 23 ]. This review summarizes the results across 25 studies, which reported on 4275 patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review also has the highest statistical power and appraises all the clinically important endpoints. The most recent reviews by Zhou et al in 2020 included 11 studies with 1107 patients [ 21 ]; other reviews by Bahbah et al in 2019 and Sutherland et al in 2018 included 9 RCTs with 1572 patients, and 14 trials with 1917 participants, respectively [ 22 , 23 ]. This review summarizes the results across 25 studies, which reported on 4275 patients.…”
Section: Discussionmentioning
confidence: 99%
“…This review is the most rigorous systematic review to date investigating olanzapine in the CINV setting. A protocol was developed prior to the commencement, risk of bias for studies were assessed, and publication bias was assessed; some or all of these three methodological elements were omitted in prior reviews [21][22][23][24][25][26][27]. This review also has the highest statistical power and appraises all the clinically important endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advances over 10 years in specific supportive care topics were identified. Antiemetics to control chemotherapy-induced emesis further improved with trials of olanzapine in combinations improving the control of chemotherapy-induced nausea as well as vomiting [ 7 ]. The introduction of oral anticoagulants simplified the management of cancer-associated thromboembolic disease [ 8 ].…”
Section: Changes In Supportive Care In the Past Decadementioning
confidence: 99%